2021
DOI: 10.5902/1980509846843
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and vegetative compatibility groups of <i>Fusarium</i> spp. pathogenic to <i>Ilex paraguariensis</i> A. St.-Hil.

Abstract: Nas regiões Centro-Oeste e Sul do Brasil, a cultura da erva-mate (Ilex paraguariensis) constitui-se uma importante fonte de extrativismo florestal, além de diversificar a renda, principalmente na agricultura familiar. A erva-mate, como outras espécies florestais, é infectada por diversos patógenos, como o gênero Fusarium, causador da podridão-de-raízes. Os patógenos possuem ampla variabilidade genética, mesmo dentro de um único gênero e dentro de uma única espécie, resultado de adaptações ao meio em que vivem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies have been done in the last decades exploring the relationship between fungi and yerba mate. Some works describe the pathogenicity of Fusarium to yerba mate as the main causal agent of root rotting disease (Mezzomo et al, 2021;Mezzomo et al, 2019), and besides Fusarium, some authors attribute this disease to Pythium and Rhizoctonia (Poletto et al, 2015;Poletto et al, 2007). Studies evaluating the phytosanitary quality of yerba mate seeds have revealed the presence of several fungi, including pathogens such as Fusarium (Oliveira et al, 2015;Souza et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done in the last decades exploring the relationship between fungi and yerba mate. Some works describe the pathogenicity of Fusarium to yerba mate as the main causal agent of root rotting disease (Mezzomo et al, 2021;Mezzomo et al, 2019), and besides Fusarium, some authors attribute this disease to Pythium and Rhizoctonia (Poletto et al, 2015;Poletto et al, 2007). Studies evaluating the phytosanitary quality of yerba mate seeds have revealed the presence of several fungi, including pathogens such as Fusarium (Oliveira et al, 2015;Souza et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%